ANNUAL BALI INTERNATIONAL COMBINED CLINICAL MEETING - Svigos, John (BALI MEDICAL JOURNAL, 2015)
Background: This valuable collaboration between Adelaide and Bali was first convened by Prof. I G. Surya, the late Prof. Made Kornia and Associate Prof. John Svigos in May 2011 at Sanglah General Hospital, Bali-Indonesia. This is a three day clinical meeting consisting of a daily Plenary Session for formal presentations running along with a Concurrent Session predominantly for “hands on” and interactive teaching. The meeting has a multidisciplinary focus which is in tune with contemporary Maternal Fetal Medicine practice and consists of obstetricians, midwives, neonatologists and obstetric anaesthetists from both cities sharing their respective experiences. From an initial modest meeting with 80 registrants this has now grown to over 300 registrants in 2015. A fourth day was trialed in 2014 in which a Field Day was incorporated into the program and enabled the overseas participants to gain some first hand experience in the workings of an orphanage (Anak Anak Bali Kids), a midwife obstetric unit (Bumi Sehat) and a level two hospital (Sanjiwani Hospital, Gianyar). Further Field Days are anticipated at future meetings. The Visiting Faculty from Australia are predominantly from the Women’s and Children’s Hospital with input from The Lyell McEwin Hospital both in Adelaide, The Royal North Shore Hospital and the Royal Prince Alfred Hospital in Sydney and the King Edward Memorial Hospital in Perth. The broader strategic aspects of the collaboration have seen the rotation of three MFM Trainees from the Trigonum (Denpasar, Surabaya and Malang) through Adelaide for two months in 2011 and 2012 as part of their MFM training. Unfortunately AusAID funding has not been forthcoming for further rotations to occur but in 2016 a multidisciplinary group from Sanglah General Hospital will be making a one week visit to the Women’s and Children’s Hospital as a forerunner to further visits. Meantime the collaborations with the Dr. Soetomo Hospital, Surabaya and the Saiful Anwar Hospital, Malang are being further strengthened with members of the Visiting Faculty also visiting the MFM units at these hospitals prior to the BICCM. The Convenors for the 2016 BICCM meeting in May will be Dr. Ryan Mulyana assisted by Dr Jaya Kusuma, Feto Maternal Division, Sanglah General Hospital and Dr Rosalie Grivell assisted by Associate Prof John Svigos, MFM Service, Women’s and Children’s Hospital.